A Direct C2‐Selective Phenoxylation and Alkoxylation of Quinoline N‐Oxides with Various Phenols and Alcohols in the Presence of H‐Phosphonate. Issue 34 (13th September 2017) - Bi, Wen‐Zhu; Qu, Chen; Chen, Xiao‐Lan; Qu, Ling‐Bo; Liu, Zhi‐Dong; Sun, Kai; Li, Xu; Zhao, Yu‐Fen
Abstract : A practical and efficient method for the synthesis of 2‐aroxy(alkoxy)quinolines has been developed by direct cross‐dehydrogenative coupling reaction between quinoline N ‐oxides and readily available phenols and alcohols in the presence of H ‐phosphonate and CCl4 under mild conditions. Abstract : Various of 2‐aroxy(alkoxy)quinolines were synthesized by the direct cross‐dehydrogenative coupling reaction of quinoline N ‐oxides and phenols and alcohols in the presence of H ‐phosphonate and CCl4 .